2020
DOI: 10.1017/rdc.2019.158
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Specific Radiocarbon Analysis of Organic Compounds from Mount Fuji Proximal Lake (Lake Kawaguchi) Sediment, Central Japan

Abstract: Differential sources of sedimentary organic compounds in a volcanic region were revealed by determining radiocarbon content (Δ14C) of organic compounds in surface sediments from Lake Kawaguchi, at the northern foot of Mount Fuji, central Japan. The Δ14C values of C16 fatty acid (−124‰) and chlorophyll a (Chl a) (−133‰) were similar to the Δ14C of dissolved inorganic carbon (DIC) in surface water (−117‰), suggesting that a significant portion of these compounds originated from modern primary producers with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 53 publications
6
15
0
Order By: Relevance
“…The 14 C age of the plant leaf within the Kg layer (2,979 ± 31 years BP) yielded a calibrated age of 3,149 ± 54 cal BP. This is almost identical to the age of the Kg eruption (3,149 ± 12 cal BP; Tani et al, 2013), which confirms the previous finding that the plant leaf remains are the most precise recorder of age in lacustrine sediments (Nakamura et al, 2012;Yamamoto et al, 2020). The 14 C offset between the C 16 fatty acid and a plant leaf from the Kg interval (1,003 ± 73 14 C years) is consistent (within error) with the C 16 fatty acid in the core top sediments (983 ± 56 years BP) and the modern lake reservoir age (1,058 ± 35 C years) estimated in June 2017 from Lake Kawaguchi surface water DIC (Δ 14 C = −117 ± 2‰; Yamamoto et al, 2020) and atmospheric CO 2 (Δ 14 C = 7 ± 3‰ [an average of CO 2 data from five stations available]; ICOS RI, 2019).…”
Section: Lake Reservoir Effect Versus Contribution Of Preaged Materialssupporting
confidence: 88%
See 2 more Smart Citations
“…The 14 C age of the plant leaf within the Kg layer (2,979 ± 31 years BP) yielded a calibrated age of 3,149 ± 54 cal BP. This is almost identical to the age of the Kg eruption (3,149 ± 12 cal BP; Tani et al, 2013), which confirms the previous finding that the plant leaf remains are the most precise recorder of age in lacustrine sediments (Nakamura et al, 2012;Yamamoto et al, 2020). The 14 C offset between the C 16 fatty acid and a plant leaf from the Kg interval (1,003 ± 73 14 C years) is consistent (within error) with the C 16 fatty acid in the core top sediments (983 ± 56 years BP) and the modern lake reservoir age (1,058 ± 35 C years) estimated in June 2017 from Lake Kawaguchi surface water DIC (Δ 14 C = −117 ± 2‰; Yamamoto et al, 2020) and atmospheric CO 2 (Δ 14 C = 7 ± 3‰ [an average of CO 2 data from five stations available]; ICOS RI, 2019).…”
Section: Lake Reservoir Effect Versus Contribution Of Preaged Materialssupporting
confidence: 88%
“…We selected C 16 , C 24 , and C 26 fatty acids as the target compounds because of their high abundance in the Lake Kawaguchi sediments, as compared to other homologs. A previous study in the surface sediment from Lake Kawaguchi revealed that the carbon in C 16 fatty acid derives from contemporary primary producers such as diatoms, whereas the C 24 and C 26 fatty acids received substantial contributions from pre‐aged materials (Yamamoto et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4c), suggesting that the values were not solely influenced by the source of organic matter and productivity within the lake. Nevertheless, we cannot fully rule out the possibility that the Suess effect may be overestimated for the d 13 C TOC since Yamamoto et al (2020) have recently reported a 14 C age of 937 ± 22 yr BP from the lake DIC in Lake Kawaguchi, suggesting potential influence of exogenous old carbon sources and groundwater.…”
Section: Spatiotemporal Changes In Sedimentation Ratementioning
confidence: 90%
“…The C 16 fatty acid can be abundantly produced by phytoplankton, as well as other organisms such as terrestrial plants, animals, and bacteria (Harwood 1996). However, identical radiocarbon isotope ratios (D 14 C) between the sedimentary C 16 fatty acid and dissolved inorganic carbon (DIC) in surface water, as well as chlorophyll a in the sediment, suggest that it originates from contemporary primary producers like diatoms (Yamamoto et al 2020).…”
Section: Compound-specific D 13 C Analysesmentioning
confidence: 99%